The Nexus Between Renewable Energy Consumption, Financial Development, and Trade Openness Based on Environmental Quality in Uganda: An Application of the ARDL - Mayanja, John Bbale; Arinaitwe, Brian; Kasaijja, Ronald; Mutenyo, John; Sengonzi, Edward Damulira (International Journal of Energy Economics and Policy, 2024)
Environmental degradation is attributed to human activities associated with economic development. This study examines renewable energy consumption (REC), financial development (FD), trade openness, and environmental quality nexus in Uganda over the period 1990-2019 using the Autoregressive Distribution Lag (ARDL). Findings show that REC improves environmental quality both in the short and long run. In addition, while trade openness is negatively related to environmental quality in the short and long run, a negative correlation exists between FD and environmental quality only in the long run. Furthermore, economic growth has a positive relationship with environmental quality in the short run while in the long run, GDP2 improves environmental quality. However, the results from the study find no statistical relationship between FDI and environmental quality, and thus neither the pollution haven nor pollution halo hypotheses are confirmed in the Ugandan case. This paper does not only recommend investing more in renewable energy development to improve the quality of the environment but also in financial sector development to support investments that promote a low-carbon and green economy.